Comparison of the asymmetries in foot posture, gait and plantar pressure between patients with unilateral and bilateral knee osteoarthritis based on a cross-sectional study - Yi Wang; Peiming Zhang; Guocai Chen; Tao Jiang; Yonggen Zou (Scientific Reports)
Abstract This study aimed to observe the characteristics of foot posture asymmetry and abnormal gait in patients with unilateral and bilateral knee osteoarthritis (KOA) and to explore the association between foot posture asymmetry, abnormal gait and the clinical symptoms and severity of KOA. Sixty patients with KOA were allocated as follows: unilateral group (UG; n = 30) and bilateral group (BG; n = 30). We accessed foot posture, foot posture asymmetry, gait and plantar pressure parameters and symmetry index, clinical symptom-related scores and disease severity, and investigated the relationship between these variables. The results showed that the overall percentage of asymmetry and severe asymmetry in foot posture were lower in BG than in UG. There was substantial asymmetry in many gait indicators within the two groups, but no significant differences were observed between the two groups. Moreover, foot posture asymmetry, multiple gait and plantar pressure parameters and symmetry indices were closely related to clinical symptoms and disease severity. In conclusion, both unilateral and bilateral KOA patients have foot posture asymmetry and gait asymmetry, but the foot posture asymmetry of the former is more severe than that of the latter. Intervention for this population should treat simultaneously both knee joints. The evaluation and monitoring of foot posture asymmetry, gait and plantar pressure parameters and symmetry indices can provide a more comprehensive and scientific basis for the prevention and treatment of KOA.